Combining approach of collocation and finite difference methods for fractional parabolic PDEs - Md. Shorif Hossan; Trishna Datta; Md. Shafiqul Islam (Partial Differential Equations in Applied Mathematics, 2024)
This research aims to estimate the solutions of fractional-order partial differential equations of spacial fractional and both time-space fractional order. For this, we use finite differences for time derivatives and the well-known collocation method for space derivatives with lower-order Bernstein polynomials as basis functions. We explain the mathematical formulations in detail. Convergence and stability analysis of the space–time fractional diffusion equation with the source term is reported subsequently. Three numerical examples are considered for demonstrating the accuracy and reliability of the proposed method.